2010
DOI: 10.1117/12.844909
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of a new angiography suite including the high resolution micro-angiographic fluoroscope (MAF); a control, acquisition, processing, and image display system (CAPIDS), and a new detector changer integrated into a commercial C-arm angiography unit to enable clinical use

Abstract: Due to the high-resolution needs of angiographic and interventional vascular imaging, a MicroAngiographic Fluoroscope (MAF) detector with a Control, Acquisition, Processing, and Image Display System (CAPIDS) was installed on a detector changer which was attached to the C-arm of a clinical angiographic unit. The MAF detector provides high-resolution, high-sensitivity, and real-time imaging capabilities and consists of a 300 μm-thick CsI phosphor, a dual stage microchannel plate light image intensifier (LII) cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…This technique has pixels sizes of 35 m m and is capable of imaging up to 30 frames per second, compared to traditional fl at panel detectors, which have pixel sizes of 194 m m or larger. 111,112 Magnetically guided angiography, currently available at some centers, uses extracranial magnets to help catheter and wire navigation. 113,114 This technology offers the potential to permit more precise intravascular navigation while shortening fl uoroscopy and procedure times.…”
Section: Future Developmentsmentioning
confidence: 99%
“…This technique has pixels sizes of 35 m m and is capable of imaging up to 30 frames per second, compared to traditional fl at panel detectors, which have pixel sizes of 194 m m or larger. 111,112 Magnetically guided angiography, currently available at some centers, uses extracranial magnets to help catheter and wire navigation. 113,114 This technology offers the potential to permit more precise intravascular navigation while shortening fl uoroscopy and procedure times.…”
Section: Future Developmentsmentioning
confidence: 99%
“…The detector is attached using a specially designed changer onto the anteroposterior (AP) C-arm of an x-ray image intensifier biplane angiographic unit (Toshiba America Medical Systems, Tustin, California) and is controlled by specially designed Lab-VIEW-based software (National Instruments Corp., Austin, TX, USA) designated CAPIDS (Control, Acquisition, Processing, and Image Display). 2 …”
Section: Microangiographic Fluoroscopementioning
confidence: 99%
“…Other features, such as region-of-interest dual-detector cone-beam computed tomography (CT), 1 were tested in animal subjects only and will be available for clinical use in the near future. 2 …”
Section: Microangiographic Fluoroscopementioning
confidence: 99%
See 1 more Smart Citation
“…Also, MAF can be used without a significant delay in the procedure, as the MAF swings into place in front of the standard AP fluoroscope. Initial patient studies have demonstrated that the use of the high-resolution MAF detector at selected points in a procedure may play an important and decisive role in clinical studies [3]. With the use of the MAF detector, tiny features of the devices such as stents, small movements of the microcatheters and coils can be seen.…”
Section: Introductionmentioning
confidence: 99%